2009
DOI: 10.1186/ar2645
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of soluble receptor for advanced glycation end products and of S100 proteins are associated with inflammatory, autoantibody, and classical risk markers of joint and vascular damage in rheumatoid arthritis

Abstract: Introduction The receptor for advanced glycation end products (RAGE) is a member of the immunoglobulin superfamily of cell surface receptor molecules. High concentrations of three of its putative proinflammatory ligands, S100A8/A9 complex (calprotectin), S100A8, and S100A12, are found in rheumatoid arthritis (RA) serum and synovial fluid. In contrast, soluble RAGE (sRAGE) may prevent proinflammatory effects by acting as a decoy. This study evaluated the serum levels of S100A9, S100A8, S100A12 and sRAGE in RA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
6
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 73 publications
7
73
6
2
Order By: Relevance
“…S100A8/A9 showed good correlations with several clinical markers of disease activity. Compared to previous studies, the levels of calprotectin measured in our study showed a better correlation with ESR nor CRP, as demonstrated in different researches (2,22,26). As well, CRP poorly correlated with other disease activity parameters.…”
Section: Discussioncontrasting
confidence: 72%
“…S100A8/A9 showed good correlations with several clinical markers of disease activity. Compared to previous studies, the levels of calprotectin measured in our study showed a better correlation with ESR nor CRP, as demonstrated in different researches (2,22,26). As well, CRP poorly correlated with other disease activity parameters.…”
Section: Discussioncontrasting
confidence: 72%
“…Regarding inflammation, a negative correlation between sRAGE and CRP, IL-6, PAI-1 and TNF-α together with a positive association with adiponectin was shown in the present study. Interestingly, serum sRAGE levels in rheumatoid arthritis patients were negatively associated with serum levels of CRP (51). It was also recently described that increased serum CRP together with reduced concentrations of sRAGE appear to be due to elevated TNF-α levels (52).…”
Section: O V E M B E R -D E C E M B E R 2 0 1 1 C a L P R O T E C T Imentioning
confidence: 93%
“…The concentration of MMP-9 to vascular damage by activating MMP-9 (42), and both HC and pentosidine were in general increased with inflammation monitored by hsCRP, both oxidative markers were neither correlated with each other, nor serum levels of hsCRP and MMP-9 in WS. Serum pentosidine and HC may be differentially regulated by inflammation as was reported (4,6,14,17,23,24,43). Although serum HC in WS did not correlate with TC, HDL-C, LDL-C, and TG (data not shown), the serum HC level in the DL(+) group in WS was significantly elevated irrespective of age compared with the DL(-) group.…”
Section: Measurementsmentioning
confidence: 53%
“…Pentosidines are a family of advanced glycation endproducts (AGEs) generated under oxidative stress and ageing (2)(3)(4)(5)(6)(7)(8). AGEs are a group of reactive intermediates resulting from a series of non-enzymatic chemical reactions after an initial glycosylation such as rearrangement, dehydration, oxidation, and fragmentation reactions of glucose or its adducts to protein (9,10).…”
Section: Introductionmentioning
confidence: 99%